A dedicated preventive protocol sustainably avoids spinal cord ischemia after endovascular aortic repair - Rosvall, Lina; Karelis, Angelos; Sonesson, Björn; Dias, Nuno V. (Frontiers in Cardiovascular Medicine, 2024)
To analyze the incidence of spinal cord ischemia (SCI) after complex endovascular aortic repair (EVAR) after the introduction of a dedicated SCI preventive protocol.Retrospective review of all consecutive patients undergoing complex EVAR with branched (BEVAR) and/or fenestrated grafts (FEVAR) during a 6-year period starting January 1 st , 2015. The preventive protocol consisted of staging extensive aortic repairs, maintaining a mean arterial pressure (MAP) > 80 mm Hg, Hb level > 110 g/L, early lower limb reperfusion and neurological control per hour during the post-operative stay in the intensive care unit (36 to 72 hours). Prophylactic cerebrospinal fluid drainage (CSFD) was used selectively. Pre-intra-, and 30day postoperative clinical data and imaging were collected. Primary end point was the development of perioperative SCI. Secondary outcome included technical and clinical success.Complex EVAR was performed in 205 patients (167 males, 72 (67-75) years, 182 (88.8%) elective) with juxtarenal aneurysms (JRA, 155 patients) or thoracoabdominal aortic aneurysms (TAAA). SCI occurred after JRA repair in two patients (1.3%, both ruptures) and after TAAA repair in three (6.0%, one rupture) (p = 0.06), all within nine hours postoperatively. There was symptom regression in three cases (one partial, two complete), resulting in a persistent SCI level of 0.6% and 4.0% for JRA and TAAA, respectively. Only one patient with persistent SCI could be discharged from the hospital alive. Patients developing SCI were more commonly female (n = 3, p =.016), presented with rupture (n = 3, p <.001), had preoperative renal insufficiency (n = 5, p <.001) and had lower minimal MAP (p = .015). No regression analysis was done due to the limited number of SCI events in relation to the study population size. Primary technical success was achieved in 162 patients (83.5%) and clinical success in 153 patients (75.4%), without any differences between the groups.The incidence of persistent SCI after complex EVAR is low with the use of a dedicated SCI preventive protocol allowing the early diagnosis. Females, patients with ruptured aneurysms and preoperative renal insufficiency are at higher risk. Further studies are needed to customize the protocols particularly in those high-risk patients.